Analisis Penggunaan Bahasa Indonesia dalam Interaksi Aktivitas Pembelajaran Siswa Sekolah Dasar - Wulandari, Nurmalita Kurnia; Muhroji (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The teacher's ability to communicate with students is one of the main factors in classroom learning. Communication is one of the factors that causes students' interest in learning, because when teachers are not good at communicating, students' enthusiasm for learning in class will decrease. The aim of this research is to describe communication between teachers and students using good and correct Indonesian in accordance with PUEBI rules at SDN 1 Tarub, so that students' interest in learning during learning can increase well. The method in this research is descriptive qualitative. The research subjects consisted of homeroom teachers and students at the elementary school. Data collection techniques include observation, interviews and documentation. Researchers use source triangulation as a data validity tool. Interactive data analysis through data reduction, data presentation and verification processes. The findings of this research show that there are two errors in learning interactions, namely phonological errors (language sounds) and spelling errors in the proper and correct use of Indonesian according to PUEBI rules. Teachers and students still use regional languages to communicate in class during learning. So, it is hoped that this research can increase and implement a sense of love for one's country by using good and correct Indonesian language communication during learning.